"Further Distance and Silence among Kin": Social Impact of COVID-19 on Older People in Rural Southeastern Nigeria. Issue 4 (2nd October 2022) - Ekoh, Prince Chiagozie; George, Elizabeth Onyedikachi; Agbawodikeizu, Patricia Uju; Ezulike, Chigozie Donatus; Okoye, Uzoma Odera; Nnebe, Ikechukwu
ABSTRACT: Given the new and unprecedented challenges faced by older people during the COVID-19 pandemic globally, this study explored the social impact of COVID-19 on older people in rural Nigeria. Data was collected from 20 older persons using in-depth interviews and analyzed thematically. Findings revealed that the pandemic has limited the rural older people's social support and social contact with loved ones, leading to their increased poverty and loneliness due to their dependence on intergenerational support. The study recommends creative ways to safely maintain connectedness with older people, and expansion of the Nigerian pension policy to ensure income security for all older people as the pandemic has exposed the unsustainability of dependence on social networks.